Associations of prenatal and childhood chlorpyrifos exposure with Neurodevelopment of 3-year-old children. (August 2019) - Guo, Jianqiu; Zhang, Jiming; Wu, Chunhua; Lv, Shenliang; Lu, Dasheng; Qi, Xiaojuan; Jiang, Shuai; Feng, Chao; Yu, Haixing; Liang, Weijiu; Chang, Xiuli; Zhang, Yubin; et al.
Abstract: Chlorpyrifos (CPF), an organophosphate insecticide, has been linked to adverse neurodevelopmental effects in animal studies. However, little is known about long-term neurotoxicity of early-life CPF exposure in humans. We aimed to evaluate the associations of both prenatal and early childhood CPF exposure with neurodevelopment of children. In this observational study based on Sheyang Mini Birth Cohort, pregnant women were recruited from an agricultural region between June 2009 and January 2010, and their children were followed up from birth to age three. Urinary 3, 5, 6-Trichloro-2-pyridinol (TCPy), a specific metabolite of CPF, was quantified using large-volume-injection gas chromatography-tandem mass spectrometry. Developmental quotients (DQs) of children in motor, adaptive, language, and social areas were assessed by trained pediatricians. Data from 377 mother-child pairs were used in the current study. Associations between CPF exposure and neurodevelopmental indicators were estimated using generalized linear models with adjustment for potential confounders. The median concentrations of TCPy in maternal and children's urine were 5.39 μg/L and 5.34 μg/L, respectively. No statistically significant association was found between maternal urinary TCPy concentrations and children neurodevelopment. While for postnatal exposure, we found lower motor area DQ score 0.61 [95% confidence interval (CI): −1.13,  −0.09; p  = 0.02] and social area DQ score 0.55 (95% CI: −1.07,  −0.03; p  = 0.04) per one-unit increase in the ln-transformed childhood urinary TCPy concentrations. Further stratification by sex indicated that the inverse associations were only observed in boys, but not in girls. Our findings suggest that adverse neurodevelopmental effects were associated with early childhood CPF exposure, but not prenatal exposure. Additional longitudinal studies are needed to replicate these results and to further understand the toxicological mechanisms of CPF. Graphical abstract: Image 1 Highlights: Chlorpyrifos (CPF) is ubiquitous in maternal and children's urinary samples. Adverse effects of postnatal CPF exposure on children's motor and social function were found. No association was observed between prenatal CPF exposure and children's neurodevelopment. Boys appeared to be more sensitive to neurotoxicity of CPF than girls. Abstract : Motor and social function of 3-year-old children were adversely associated with childhood rather than prenatal exposure to chlorpyrifos.